Morphological and agronomical characters of four black rice varieties from West Kalimantan, Indonesia: - - TANTRI PALUPI; FRANKY PANGARIBUAN; HEARNES; FADJAR RIYANTO; WASIAN; DWI ZULFITA (Society for Indonesian Biodiversity, 2020)
Abstract. Palupi T, Pangaribuan F, Hearnes, Riyanto F, Wasian, Zulfita D. 2020. Morphological and agronomical characters of four black rice varieties from West Kalimantan, Indonesia. Biodiversitas 21: 1065-1073. The black rice paddy is a variety of rice known to have anthocyanin content which is beneficial to human health. Yet, the black rice paddy is relatively rare to find as not all rice-growing areas develop and plant black rice. West Kalimantan has several potential black rice varieties which are potentials as genetic resources to create a new black rice variety in plant breeding programs. This research was aimed to describe the morphological and agronomical characteristics of four black rice varieties from West Kalimantan, namely Nanga Taman, Mukok, Senakin, and Ensalang. The study was conducted at the experimental garden of Agriculture Faculty, University of Tanjungpura, Pontianak using Completely Randomized Design. Each variety consisted of six replications, and each replication consisted of 3 samples. We observed 12 characters of the vegetative phase and 21 characters of the generative period. The four varieties had similarities in 13 characters and differences in 20 characters. The results showed that the four black rice had superior properties such as the stem angle and the angle of the leaves is upright so that it reduces interference from bird pests. Among them, the Senakin variety had an advantage over the three other varieties in terms of plant height, age, the number of productive tillers, and weight of grains.